ANTECEDENTS OF PATIENT SATISFACTION AND ITS IMPACT ON WORD OF MOUTH: A STUDY ON OUTPATIENTS AT XYZ PRIVATE HOSPITAL IN MAKASSAR CITY - Ellen, Ellen; Bernarto, Innocentius (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
The objective of this research is to determine the influence of antecedents of patient satisfaction in outpatient services on word of mouth. The antecedents of patient satisfaction will be assessed from the factors of people, process, and physical evidence, which are elements of the marketing mix. This is a quantitative study, where the data collection method involves distributing questionnaires to sample respondents within the research population. Four hypothesis pathways were analyzed using PLS-SEM, with primary data collected from outpatient patients at private hospital XYZ in Makassar city in April 2023, with total of 208 respondents. The results show that the factors of people, process, and physical evidence positively influence patient satisfaction and also have a positive impact on word of mouth. This research is expected to contribute to private hospitals in improving their outpatient services, enhancing word of mouth, and also elevating the hospitals’ image.